Identification of the model elements for evaluating the management activities of an industrial enterprise based on KPI specification. (July 2020) - Kukartseva, O I; Lobkov, K Yu; Tynchenko, S V; Fedorova, N V; Boyko, A A; Danilchenko, Yu V
Abstract: This article summarizes modern methods of evaluating the marketing activities of an industrial enterprise and on this basis, identifies the possibilities of using the concept of a balanced scorecard for a comprehensive assessment and its results. These elements serve as the basis for drawing up a model for assessing the management activities of an industrial enterprise. In the study of the relationship between the prospects of the MBSC and the prospects of the key indicators of achievement, it was determined that the marketing mix should include four marketing sub-mixes (product mix, contract mix, communication mix, distribution mix). Each sub-mix is a key indicators of achievement perspective. As a result of these studies, on the basis of prospects, their optimal ratio was found to solve a specific tactical or strategic task of developing the key indicators of achievement. This topic is relevant, since marketing is the most difficult to manage area of the enterprise and therefore it is necessary to use various models and methods for assessing the effectiveness of various factors that help identify diverse problems and coordinate movement towards goals.